AKTIVITAS PREBIOTIK POLISAKARIDA LARUT AIR BIJI DURIAN IN VITRO PADA Lactobacillus plantarum, L. acidophilus dan Bifidobacterium longum - Ledy Purwadani; Fenny Imelda; Libertus Darus (Universitas Tanjungpura, 2018)
Durian seeds are waste from durian fruit that has not been utilized optimally. Durian seed waste has a carbohydrate content of 46.2% and allows it to be used as a new prebiotic source, including the possibility of oligosaccharide compounds and water soluble polysaccharide compounds (PLA). The aim of this study was to determine the prebiotic activity of crude extract of PLA in probiotic bacteria Lactobacillus plantarum and Bifidobacteria longum in vitro. The durian seeds used come from the Karangan Hall obtained from the Mawar Market in Pontianak. This study consists of several stages, namely: 1) Extraction of crude extract of PLA durian seeds; 2) Potential testing of prebiotics in PLA durian seeds; and 3) Calculating the value of prebiotic activity of PLA durian seeds. The results showed that the yield of durian seed PLA was 1.59%, with the value of prebiotic activity against bacteria L. acidophilus (0.547), L. plantarum (0,921), and B.longum (0,187). PLA durian seeds have been applied to synbiotic drinks. PLA durian seeds have the potential as a prebiotic source and can be applied to synbiotic drinks.